Using Nomor Acak Learning Models of Physics Students in the FKIP of Riau University - Zufriady, Zufriady; Syahrilfuddin, Syahrilfuddin; Santika, Runi; Yohana, Reni (Proceedings of the UR International Conference on Educational Sciences, 2018)
Learning models that are always evolving make researchers interested in developing to learning models. This research try to introduce nomor acak learning models to physics students in the FKIP of Riau University to Management Education course. Nomor acak models is a learning model that emphasizes that students are active during the learning process, this model has been designed before its and is still tried in a small scope. This research uses action research method by describing all activities carried out during one semester in accordance with the stages of the model with the steps of preparation, implementation, evaluation, conclusion and motivation. From the results of the implementation for one semester the average grades of class A and B are as follows: midterm exam 85.14, final exams 81.83, Weight, 84.5, Obtaining a value of A17.5 (45.46%), Value of A-16, 5 (42.85%), Value of B+ 4.5 (11.68%). From the learning outcomes that appear after the end of this semester it can be seen that the nomor acak learning models is able to increase the value of students.